Sweden : Financial Sector Assessment Program Update: Detailed Assessment of Observance on Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper discusses the current state of Swedish implementation of the Basel Core Principles for Effective Banking Supervision (BCP). The banking supervisory framework and its implementation in Sweden are in line with many of Basel Core Principles' essential criteria. However, the assessors found evidence of impairment in Finansinspektionen (FI)'s operational independence. Assessors suggest that staffing levels at FI are an urgent concern to be remedied and also that a revised legal structure ensuring greater independence of FI be considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet